Factors Associated with the Implementation of GERMAS (Healthy Living Community Movement) in the Community of Cengkareng Timur Village - Manurung, Evanny Indah; Sianturi, Laura Angelia Putri; Purba, Lola Ade Syah Putri; Agustina, Mutia; Silitonga, Ester (Public Health of Indonesia, 2024)
Background: Healthy Community Movement (GERMAS) is a systematic and planned effort carried out jointly by the entire nation with awareness, willingness, and ability to behave healthily to improve quality of life. Based on the results of preliminary studies of visitors of the Cengkareng Health Center who live in the East Cengkareng area, it was found that the application of GERMAS in the Cengkareng community was still relatively insufficient and the number of Non-Communicable Diseases (NCDs) increased. Objective: This study aimed to identify factors associated with the implementation of GERMAS in East Cengkareng Village  Methods: This study used a quantitative and correlational approach with a cross-sectional design. The population of this study is the East Cengkareng Community of adults aged 20-49 years. An accidental sampling technique was used to obtain 300 respondents. This research instrument was adopted from previous research conducted by Laksmi in 2019 to measure the implementation of GERMAS, attitude, and knowledge. The data obtained were analyzed using univariate analysis and bivariate analysis with Chi-Square. Results: The results showed that the people in the East Cengkareng village as many as 252 (84.0%) respondents implemented GERMAS well and as many as 48 (16.0%) respondents did less implement GERMAS. The factors that have a significant relationship with the implementation of GERMAS are age (p-value=0.004), occupation (p-value=0.023), and attitude (p-value=0.013) Conclusions: Age, occupation, and attitude can affect GERMAS implementation. Future researchers can analyze the application of GERMAS on different characteristics of respondents such as the elderly, pregnant women, adolescents, and on respondents with certain conditions. Keywords: Age; attitude; GERMAS; occupation